Reliability and Validity of a Pool-Based Maximal Oxygen Uptake Test to Examine High-Intensity Short-Duration Freestyle Swimming Performance. Issue 5 (May 2019) - Nagle, Elizabeth F.; Nagai, Takashi; Beethe, Anne Z.; Lovalekar, Mita T.; Zera, Jacquelyn N.; Connaboy, Christopher; Abt, John P.; Beals, Kimberly; Nindl, Bradley C.; Robertson, Robert J.; Lephart, Scott M.
Abstract : Abstract: Nagle, EF, Nagai, T, Beethe, AZ, Lovalekar, MT, Zera, JN, Connaboy, C, Abt, JP, Beals, K, Nindl, BC, Robertson, RJ, and Lephart, SM. Reliability and validity of a pool-based maximal oxygen uptake test to examine high-intensity short-duration freestyle swimming performance. J Strength Cond Res 33(5): 1208–1215, 2019—A modality-specific swimming protocol to assess maximal oxygen uptake (VO2 max sw ) is essential to accurately prescribe and monitor swimming conditioning programs. Consequently, there is a need for a reliable and valid graded intensity swimming pool test to accurately assess VO2 max sw using indirect calorimetry. The purpose of this study was to assess (a) reliability of an intensity self-regulated swimming pool test of VO2 max sw and (b) validity of a VO2 max sw test using performance swim (PS) time as the criterion. Twenty-nine men ( n = 15) and women ( n = 14) (age, 23 ± 6.4 years; body mass index, 23.5 ± 3.0 kg·m −2 ) performed 2 swimming pool VO2 max sw trials (VO2 max sw A and VO2 max sw B), and 2 PS tests (45.7 m [31.20 ± 4.5 seconds] and 182 m [159.2 ± 25.5 seconds]). For test-retest reliability (trials A vs. B), strong correlations ( p < 0.05) were found for VO2 max sw (ml·kg −1 ·min −1 ) ( r = 0.899), O2 pulse (ml O2 ·beat −1 ) ( r = 0.833), and maximum expired ventilatory volume (L·min −1 ) ( r = 0.785). For performance validity, moderately strong correlations ( p < 0.05) were found between VO2 max sw A and 45.7-m ( r = −0.543) and 182-m ( r = −0.486) swim times. The self-regulated graded intensity swimming pool protocol examined presently is a reliable and valid test of VO2 max sw . Studies should consider the suitability of a VO2 max sw test for military personnel, clinical populations, and injured athletes.